Closed user group mobile phone platforms to enhance communication and coordination of One Health activities in Kenya - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
In 2021, the platforms were piloted and initial results summarized in a project report to the funder (USAID) as part of the Accelerated Value Chain Development Project. Monitoring and adaption will continue after A4NH ends. Evidence link points to the project website which describes the innovation.